Cim and Bayezid II, Mohammad the Conqueror's sons, and their Conflict for the Throne A Study of the Struggle-Reasons for the Throne and its effects on the Domestic State of the Ottoman State in the Reign of Sultan Bayezid II (1481-1512) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Struggle for the throne in the Ottoman State started since it was created. Ottoman sultans tried by all available ways to protect their positions. This explains the various preventive measures, they adopted, to protect their thrones. Relying on 'religious fatwa' Mohammad the Conqueror issued his law which allowed him to kill his brothers in order to prevent disfigurement of the national unity. This law stayed in use for a century, till it was replaced by a new law: keeping all princes under repressive home arrest in the suites In the palace, called cages. The children of the present sultan were exempted from this treatment. This struggle led to many civil wars which contributed to the decline of the Ottoman State, like the ferocious conflict between the two sons of Sultan Mohammad the Conqueror.